Sikh art and literature - Brown, Kerry 1958- (London New York Routledge, 1999)
"Sikh Art and Literature traverses the 500-year history of a religion that dawned with the modern age in a land that was a thoroughfare of invading armies, ideas and religions and arts of East and West. The poetry of the scriptures, the illustrated life stories of Guru Nanak, the early paintings from various artistic schools and regions, the dazzling treasuries of the Sikh kingdoms, the romantic artworks of visiting European dignitaries, and the serenity of Sikh sacred architecture all provide doorways to this heroic and revolutionary faith."--Jacket.
From Gurus to Kings / Early and court painting / Gursharan Singh Sidhu -- an illustrated life: Guru Nanak in narrative art / Robert J. Del Bontà -- The Sikh treasury? The Sikh kingdom and the British Raj / Susan Stronge -- Golden temple, marble forum: Form and meaning in scared architecture / Henry J. Walker -- The unstruck melody / Musical mysticism in the scripture / Gobind Singh Mansukhani -- The western gateway to Sikhism : The life and works of Max Arthur Macauliffe / Harbans Lal -- Poetry urges poetry: From the Guru Granth to Bhai Vir Singh / Nikky-Guninder Kaur Singh -- Critical ecstasy: The modern poetry of Puran Singh / Surjit Singh Dulai -- Old culture, new knowledge: The writings of Bhai Mohan Singh Vaid / Ardaman Singh and Nirvikar Singh -- A mirror to our faces : The short stories of Khushwant Singh / Abdul Jabbar.
"In collaboration with the Sikh Foundation."
Includes bibliographical references (pages 206-209) and index.
Keywords: Sikh art; Hindu art -- India -- Punjab; Sikh literature